Suspension and Interruption of the Effects of the Employment Agreement: Is There Anything new in the Pandemic? (Revista Justiça do Direito, 2021)
This article, based on the author's research project on the effectiveness and effectiveness of the Constitution and Fundamental Rights to work and work, carried out in the Postgraduate Program in Law at the Pontifical Catholic University of Rio Grande do Sul, The text approaches the institute of the suspension and interruption of the employment agreement from its classic concept. With the approach, we examine the emergency legislation that, among other hypotheses for preserving employment and income, listed the suspension of the employment agreement. The question is: has the pandemic changed the concept of suspension of the employment agreement?